What is the Comfort Distance for a Human and a Collaborative Industrial Robot Interaction? - Azevedo, Helio; Batista, Murillo Rehder; Barbizan, Ana Carolina Santos; Nunes, Guilherme Bitencourt; Ramos, Josue Junior Guimaraes; BeraldoFilho, Germano (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
Humans interact with each other considering a complex mechanism of analysis defined by the fusion of cultural factors with a set of non-verbal factors such as kinesics, haptics and visual cues. This behavior is termed proxemics, with interpersonal distance being its most expressive signal. When interacting with robotic agents, proxemic behavior must also be considered while respecting the human need to maintain a comfortable distance. This study explores the hypothesis that the comfort distance decreases as there is a common interest activity underway. To validate this hypothesis, a human-robot interaction experiment was conducted where the common interest is achieved through a card game. In addition to the quantitative data, such as the robot's distance, the experiment also generates qualitative data through subjects' responses to a questionnaire about their impressions of the interaction. The analysis of the experiment results is of particular interest in industrial plants where the use of collaborative mobile robots (cobots) represents a growing demand in the sector.